Towards balanced international growth : Essays presented to J. Tinbergen - Tinbergen, Jan; Bos, Hendricus Cornelis (Amsterdam ; London : North-Holland Pub. Co., 1969)
This volume is a Festschrift in honour of Professor Tinbergen on his retirement as Director of the Netherlands Economics Institute. The volume comprises essays colleagues and disciples who have worked with him mainly on development problems contribute a wide variety of essay.
Includes bibliographies.
lje 13/12/18
Loans
Keywords: Economic development; Developing countries